Aerodynamics of ski jumping: experiments and CFD simulations - Meile, W.; Reisenberger, E.; Mayer, M.; Schmölzer, B.; Müller, W.; Brenn, G (Experiments in Fluids, 2006)
The aerodynamic behaviour of a model ski jumper is investigated experimentally at full-scale Reynolds numbers and computationally applying a standard RANS code. In particular we focus on the influence of different postures on aerodynamic forces in a wide range of angles of attack. The experimental results proved to be in good agreement with full-scale measurements with athletes in much larger wind tunnels, and form a reliable basis for further predictions of the effects of position changes on the performance. The comparison of CFD results with the experiments shows poor agreement, but enables a clear outline of simulation potentials and limits when accurate predictions of effects from small variations are required.